Hesperidin alleviated D-GalN/LPS induced acute liver injury in mice: insights into gut microbiota and the Nrf2/Keap1 pathway - Li, Kaiming; Hou, Gaohuan; Deng, Hongbin; Lu, Weiting; Liu, Hongyou; Li, Weiqin; Wang, Qi; Tong, Zhihui (Frontiers in Microbiology, 2025)
BackgroundAcute liver injury (ALI) has grown to be a major worldwide health issue, yet current therapeutic approaches remain inadequate. A growing number of studies suggest that hesperidin demonstrates high therapeutic potential in the treatment of acute liver injury. However, the specific mechanisms by which hesperidin alleviates ALI remain unclear. Herein, we aimed to investigate how hesperidin ameliorates acute liver injury under conditions that influence the gut microbiota.MethodsA mouse model of ALI was established by D-GalN/LPS injection, and 16S rDNA sequencing was employed to explore the underlying mechanism of hesperidin in alleviating ALI. Forty mice were divided into the control group (CON), the LPS&D-GalN group (ALI), the HDN group (feed hesperidin), the HDA group (the positive drug group, feed hesperidin). Liver, ileum, and serum samples were collected randomly from five mice in each of the four groups to evaluate liver injury markers, inflammatory indicators, intestinal barrier function indices, and antioxidant parameters. Additionally, cecum contents were collected for 16S rDNA sequencing to analyze the gut microbiota.ResultsHesperidin significantly ameliorated D-GalN/LPS-induced abnormal transaminase activities, liver and intestinal systemic inflammation, and intestinal environmental disorders. Furthermore, activation of the Nrf2/Keap1 signal pathway by HDN reduced the production of proinflammatory cytokines (TNF-α, IL-1β and IL-6) and boost the activity of antioxidant enzymes (CAT and SOD). HDN restored SCFAs to normal levels by upregulating the abundance of beneficial bacteria (Lachnospiraceae_NK4A136_group, Alloprevotella and Clostridia_UCG-014). The alleviation of ALI by HDN occurs through protection of the intestinal mucosal barrier and reduction of LPS permeating in serum. The decrease in LPS inactivates the Nrf2/Keap1 signaling pathway and prevents inflammation.ConclusionHesperidin as a promising natural compound capable of modulating the gut–liver axis and strengthening endogenous antioxidant mechanisms, providing valuable insight into its potential therapeutic application in acute liver injury.